Optimizing safe rates of pop-up inorganic starter nitrogen and potassium fertilizers for maize - Makaza, William; Khiari, Lotfi; El Achaby, Mounir (Frontiers in Agronomy, 2025)
Applying starter nitrogen (N) and potassium (K) fertilizers in a pop-up placement directly in the maize seed furrow is a delicate practice due to the direct contact between fertilizers and seeds. This proximity increases the risk of seed damage caused by the salinity of N and K fertilizers and the ammoniacal toxicity of nitrogen fertilizers. This study aims to determine the safe application rates of four commonly used starter fertilizers: monoammonium phosphate (MAP: NH4H2PO4), diammonium phosphate (DAP: (NH4)2HPO4), potassium chloride (KCl), and potassium sulfate (K2SO4) across three soil textures: fine (G1), medium (G2), and coarse (G3). A greenhouse experiment was conducted using a three-factor factorial design (four fertilizer sources, five application rates, and three soil textures) arranged in a randomized complete block design. ANOVA revealed significant effects of fertilizer source, application rate, soil texture, and significant two-way interactions between these factors. Polynomial contrasts of maize germination rates in response to increasing fertilizer doses allowed us to establish the maximum safe rates: i) DAP: 3 kg N ha-¹ in G1, 0.8 kg N ha-¹ in G2 and G3; ii) MAP: 5–7 kg N ha-¹ regardless of soil texture; iii) KCl: 10 kg K ha-¹ in G1, 14 kg K ha-¹ in G2 and G3; K2SO4: >16 kg K ha-¹ regardless of soil texture. The experiment also identified visual signs of toxicity, mainly associated with nitrogen fertilizers. These included delayed and reduced emergence, leaf chlorosis, necrotic roots and seeds, stunted and grooved coleoptiles, and, at high doses, seedling mortality. Other quantitative performance indicators, such as shoot and root biomass, chlorophyll readings, and early vigor, were strongly correlated with germination rates and supported the same conclusions regarding safe fertilizer rates. These findings provide practical recommendations for agronomists and farmers to optimize starter fertilizer management in maize by selecting appropriate application rates and fertilizer sources.